Mediation effect of cord blood cortisol levels between maternal prepregnancy body mass index and birth weight: a hospital-based cross-sectional study - Nisanth Selvam; Jayashree K; Prasanna Mithra (The Korean Pediatric Society, 2022)
Background Changes in maternal weight affect the maternal and fetal hypothalamic-pituitary-adrenal axis, influencing birth weight and contributing to the fetal origin of adult diseases (Barker's hypothesis). This study primarily focused on cord blood cortisol levels and identified the association between maternal prepregnancy body mass index (pre-BMI) and birth weight. It also assessed cord blood lipid profile changes related to maternal pre-BMI, birth weight, and cord blood cortisol levels. Purpose To study the mediation effect of cord blood cortisol level between maternal pre-BMI and birth weight and its correlation with cord blood lipid profile. Methods A total of 169 maternal-neonatal pairs were included at 2 tertiary care centers. Mediation analysis was used to estimate the extent of the association between maternal weight changes and birth weight. Results For each unit increase in maternal pre-BMI, birth weight increased by 90.5 g; for every kilogram increase in gestational weight, birth weight increased by 128.44 g. No considerable mediation effect of cortisol was found between pre-BMI and gestational weight gain or between rate of weight gain and birth weight. Pre-BMI and birth weight had a significant negative correlation with high-density lipoprotein cholesterol (HDL-C) levels, i.e., HDL-C was decreased by 1.1 mg/dL for every unit increase in BMI (P=0.017) and for every 100-g increase in birth weight, HDL-C decreased by 0.6 mg/dL (P=0.046). A significant positive correlation was found between cord blood lipid profile and cortisol levels, especially HDL-C (P=0.041). Conclusion Cord blood cortisol levels did not mediate the association between maternal weight change and birth weight. A positive correlation was noted between cord blood cortisol levels and HDL-C level. Cord blood HDL-C level was negatively correlated with maternal pre-BMI and birth weight.